Implementation of the Family Hope Program in Oelpuah village, Central Kupang district, Kupang regency - Markus Tae; Paulus Nd.LT Ratoebandjoe; Ernawati Daeng (Goodwood Publishing, 2021)
Purpose: The purpose of this research is to find out Implementation Family Hope Program (PKH) in Oelpuah Village, Central Kupang District, Kupang Regency. Research methodology: The type of research used by researchers in this research is descriptive research with a qualitative approach. Results: The results of this study indicate that the Family Hope Program (PKH) is very beneficial for beneficiary households, particularly in the fields of education and health. However, there are still several obstacles that must be resolved so that this program can be better. Limitations: This study only focuses on the implementation of the Family Hope program (PKH) in Oelpuah Village, Central Kupang District, Kupang Regency. Contribution: The results of this research can be used as reference and evaluation in the development of the Family Hope Program (PKH). Keywords: Family Hope Program (PKH), Implementation, Public policy